Frontostriatal functional connectivity and striatal dopamine synthesis capacity in schizophrenia in terms of antipsychotic responsiveness: an [18F]DOPA PET and fMRI study. Issue 15 (21st November 2018) - Kim, Seoyoung; Jung, Wi Hoon; Howes, Oliver D.; Veronese, Mattia; Turkheimer, Federico E.; Lee, Yun-Sang; Lee, Jae Sung; Kim, Euitae; Kwon, Jun Soo
Abstract: Background: Given that only a subgroup of patients with schizophrenia responds to first-line antipsychotic drugs, a key clinical question is what underlies treatment response. Observations that prefrontal activity correlates with striatal dopaminergic function, have led to the hypothesis that disrupted frontostriatal functional connectivity (FC) could be associated with altered dopaminergic function. Thus, the aim of this study was to investigate the relationship between frontostriatal FC and striatal dopamine synthesis capacity in patients with schizophrenia who had responded to first-line antipsychotic drug compared with those who had failed but responded to clozapine. Methods: Twenty-four symptomatically stable patients with schizophrenia were recruited from Seoul National University Hospital, 12 of which responded to first-line antipsychotic drugs (first-line AP group) and 12 under clozapine (clozapine group), along with 12 matched healthy controls. All participants underwent resting-state functional magnetic resonance imaging and [ 18 F]DOPA PET scans. Results: No significant difference was found in the total PANSS score between the patient groups. Voxel-based analysis showed a significant correlation between frontal FC to the associative striatum and the influx rate constant of [ 18 F]DOPA in the corresponding region in the first-line AP group. Region-of-interest analysis confirmed the result (control group: R 2 = 0.019, p = 0.665; first-line AP group: R 2 = 0.675, p < 0.001; clozapine group: R 2 = 0.324, p = 0.054) and the correlation coefficients were significantly different between the groups. Conclusions: The relationship between striatal dopamine synthesis capacity and frontostriatal FC is different between responders to first-line treatment and clozapine treatment in schizophrenia, indicating that a different pathophysiology could underlie schizophrenia in patients who respond to first-line treatments relative to those who do not.